LINGUA FRANCA IN THE LINGUISTIC LANDSCAPE OF GRESIK KOTA BARU (GKB) - Adinda Rizki Ramadhani (ETNOLINGUAL, 2018)
In multilingual society, a language that the majority of people understand is in need. That kind of language in sociolinguistics is known as lingua franca. Lingua franca does not only appear in the way people communicate with each other, but also in the linguistic landscape of a site. By applying qualitative method, this study analyzes 48 restaurants’ names as the linguistic landscape in Gresik Kota Baru (GKB), a business center in Gresik Regency. Additionally, this study attempts to identify the most-used language in that area as well as to see which language roles as the lingua franca in the linguistic landscape of GKB. In results, it is discovered that Bahasa Indonesia acquires the highest number of occurrence, which is in 27 restaurants, whilst English are spotted in 21 restaurants’ names. In other words, the result implies that in GKB, seen from the restaurants’ names as the linguistic landscape, the lingua franca is Bahasa Indonesia.